Urban transformations in Rio de Janeiro : development, segregation, and governance - Ribeiro, Luiz Cesar de Queiroz (Springer, 2017)
This book provides an overview of urban transformations taking place in the city of Rio de Janeiro, Brazil in the last three decades. It analyses urban dynamics within the metropolis and its relationship with Brazilian urban networks. This book is structured in three main parts with sixteen chapters written by researchers from the Brazilian Metropolitan Observatory in Rio de Janeiro. The aim of the book is to study urban transformation and stagnation with regards to urban mobility and infrastructure, social analysis of territory, housing and housing market, metropolitan governance, demography, residential segregation and inequality of opportunities, among other topics.
Keywords: City planning -- Brazil -- Rio de Janeiro.; Urban renewal -- Brazil -- Rio de Janeiro.; Brazil -- Rio de Janeiro.; elektronické knihy; electronic books